THE ANALAYSIS OF CONCEPT “EVIL” IN ENGLISH FANTASY - Nasritdinov Ulugbek Ulmas ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This research delves into the concept of evil as portrayed in English fantasy literature. By examining a selection of notable works in the genre, including "Frankenstein," "The Picture of Dorian Gray," and "Dracula," this study investigates how evil is conceptualized and represented in these narratives. Drawing upon literary analysis, the research explores the symbolic manifestations, moral implications, and societal critiques offered by these works. The analysis also delves into the complex characters that personify evil, their motivations, and the influence they exert on the fantastical fictional worlds they inhabit. By understanding the varying ways in which English fantasies depict evil, this research sheds light on the intricate interplay between darkness and light, morality and corruption, within the imaginative realms of these beloved literary creations. Ultimately, this study illuminates the enduring relevance and significance of the concept of evil in English fantasy literature, providing insights into the human condition and offering both entertainment and thought-provoking contemplation for readers and scholars alike